AVALIAÇÃO DAS CONDIÇÕES PERIODONTAIS EM PACIENTES COM PARACOCCIDIOIDOMICOSE: ANÁLISE CLÍNICA E MICROBIOLÓGICA - Alana Oswaldina Gavioli Meira dos Santos (2022)
Paracoccidioidomycosis (PCM) is a fungal disease endemic in Latin America that has been considered a associated fator for periodontitis. The objective of this study was to evaluate periodontitis as well as periodontal microbiota and oral health self-perception in patients with PCM. Fifteen patients with PCM were evaluated from June to December 2021. Those with comorbidities that could favour periodontitis were excluded, such as diabetes mellitus or Aids. The patients underwent periodontal, radiographic, and microbiological analyses of material collected from the periodontium by culture or polymerase chain reaction. The identification was done by phenotypic methods. Self-perceived oral health was assessed through the Oral Health Impact Profile (OHIP-14).The median age was 57 [1st Q 54.6; 3rd Q 61.6] years, and the patients were predominantly men (86.7%) and smokers (93.3). The plaque index was high (median 73.5; 1st Q 71.9; 3rd Q 90.8), periodontitis was observed in all patients, and 73.3% of them had periodontitis of stage 3-4. The genera Capnocytophaga, Prevotella, Fusobacterium, Actinomyces, and Enterococcus were present in 93.3%, 86.7%, 86.7%, 80.0% and 73.3% of patients, respectively. The genus Candida was observed in 80.0% of patients. There was a positive correlation between the periodontal index and colony-forming units of F. nucleatum (R = 0.67; p < 0.05) and F. necrophorum (R = 0.66; p < 0.05). The median OHIP score was 13 [1st Q 5; 3rd Q 22], showing a dissatisfaction of the participants with their oral health.Most of the patients had advanced periodontitis and were dissatisfied with their oral health. The microbiota found did not differ from the microbiota reported in periodontitis in general. Descriptors: Paracoccidioidomycosis; Periodontitis; Microbiology; Oral Health.